Airway stent: what is new and what should be discarded - Herth, Felix; Eberhardt, Ralf (Current opinion in pulmonary medicine, 2016)
Purpose of reviewPatients with lung cancer often develop endobronchial disease, endobronchial tumor extension or airway compression. Various nonmalignant diseases can also lead to severe central airway obstruction.Since the early 1980s, technical advances of interventional bronchoscopic techniques h
Gesehen am 12.05.2020